Part 1, intelligent data capture: a trend only beginning - Smallwood, Robert (KM world, 2006)
Intelligent data capture (IDC), also referred to as intelligent document recognition, is the ability to scan document or electronic pages that have no fixed layout and extract data from specific fields to populate a database or business system. The IDC marketplace has its roots in basic scanning and document capture, pioneered by firms like DICOM Group's subsidiary Kofax, EMC's Captiva and ReadSoft. The competition in the market is intense, and how it plays out is not clear at this stage. ABBYY centers its business on document recognition, data capture and linguistic technologies. Brainware's A/P-distiller product is designed to handle large invoice volumes and particularly shines in table extraction. EMC Captiva has traditionally focused on larger deals in the higher end of the marketplace. Today, the focus is moving downstream to more middlemarket companies, but being able to process unstructured and semi-structured documents using IDC brings about a wealth of new opportunities. ReadSoft DOCUMENTS for Invoices can automatically post transactions with no human intervention.